MANAJEMEN MUTU PEMBELAJARAN DI SMKN 1 ROTA, BAYAT, KLATEN, SEBAGAI PUSAT KEUNGGULAN DALAM BIDANG BATIK DAN KERAMIK TAHUN PELAJARAN 2013/2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to: (1) determine the quality of learning management processes developed by SMKN 1 ROTA Bayat batik and ceramics in the field of academic year 2013/2014; (2) look at the constraints faced in teaching quality management, as well as solutions solve.This research is a descriptive qualitative performed through the data collection phase by observation, interview and documentation studies, followed by data analysis and checking the validity of data triangulation.Research conclusions are: (1) quality management process of learning batik and ceramics at SMKN 1 ROTA Bayat, pretty good start of planning, organizing, implementation, and evaluation of learning, both in learning materials, teachers, students, media and tools, as well as the mentoring process ; (2) the existence of obstacles encountered a teacher who has not entirely permanent teachers (PNS) with all its consequences, social and economic background of students, as well as operating costs and supporting infrastructure goes. With the handover management in Local Government, several obstacles still have not accumulated the solution. It is recommended: (a) management educators better, (b) assisting students with scholarships and additional competitive activity raised achievement, (c) various connections with the various parties can overcome the obstacles of human resources (teachers and students), funding and infrastructure and other operational constraints, such as the provincial and federal governments, universities, institutions concerned with education, the private sector (industry-related) and so forth.